Spatial Information Technology for Disaster Management - Mamat, Rohaya; Mansor, Shattri; Poy, Tee Tuan (Universiti Putra Malaysia Press, 2001)
Most major geohazards such as floods, forest fire and oil spills occur suddenly, and require an immediate response. This paper describes the development and establishment a spatial information technology and engineering system that uses GIS and Remote Sensing technologies to detect, monitor and assess geohazards, including floods, forest fire and oil spills. The potential application of Remote sensing and GIS techniques for floods and oil spills is discussed. The oil spill risk management system study was developed for coastal zone of Peninsular Malaysia. The development of GIS database used remotely sensed data from Landsat TM, SPOT Panchromatic and MSS, AVHRR and air-borne images. For the flood studies, Digital Elevation Model (DEM) was created for Klang River Basin from the input data of contour lines. DEMs stored the data for the slope analysis, terrain analysis and also visualizing for the flood simulation. SCS TR-55 Model was used to predict the extent of inundation and depth of flooding. Parameters of rainfall, landuse and hydrological relief were adopted as the main input data. These two case studies will provide the technical guidelines for in-depth study in GIS and remote sensing for disaster management